1341. Relative Vaccine Effectiveness Against Influenza-related Hospitalizations and Respiratory Events During the 2019/20 Influenza seAson in U.S. Children and Adults. A Real-World Evidence Comparison Between Quadrivalent Cell-based and Egg-based Influenza Vaccines. (4th December 2021) - Pelton, Stephen I; Postma, Maarten; Divino, Victoria; Mould-Quevedo, Joaquin F; Anupindi, Ruthwik; DeKoven, Mitchell; levin, myron J
Abstract: Background: Non-egg-based influenza vaccine manufacturing reduces egg adaptation and therefore has the potential to increase vaccine effectiveness. This study evaluated whether the cell-based quadrivalent influenza vaccine (QIVc) improved relative vaccine effectiveness (rVE) compared to standard-dose egg-based quadrivalent influenza vaccine (QIVe-SD) in the reduction of influenza-related and respiratory-related hospitalizations/emergency room (ER) visits among subjects 4-64 years old during the 2019/20 influenza season. Methods: A retrospective analysis was conducted among subjects 4-64 years old vaccinated with QIVc or QIVe-SD using administrative claims data in the United States of America (U.S.) (IQVIA PharMetrics ® Plus). Inverse probability of treatment weighting (IPTW) was used to adjust for baseline confounders. Post-IPTW, the number of events and rates (per 1, 000 vaccinated subject-seasons) of influenza-related hospitalizations/ER visits, respiratory-related hospitalizations/ER visits and all-cause hospitalizations were assessed. Poisson regression was used to estimate adjusted rVE. To avoid any influenza outcome misclassification with COVID-19 infection, the study period ended March 7, 2020. A sub-analysis for a high-risk subgroup was conducted. Urinary tract infection (UTI) hospitalization was assessed as a negative control endpoint. Results: During the 2019/20 influenza season, 1, 150, 134 QIVc and 3, 924, 819 QIVe-SD recipients were identified post-IPTW. Overall adjusted analyses (4-64 years old) found that QIVc was associated with a significantly higher rVE compared to QIVe-SD against influenza-related hospitalizations/ER visits (5.3% [95% CI: 0.5%-9.9%]), all-cause hospitalizations (14.5% [95% CI: 13.1%-15.8%]) and any respiratory-related hospitalization/ER visit (8.2% [95% CI: 6.5%-9.8%]). A similar trend was seen for the high-risk subgroup; for instance, rVE for QIVc compared to QIVe-SD against influenza-related hospitalizations/ER visits was 10.5% [95% CI: 2.9%-17.4%]. No effect was identified for the negative control outcome. Conclusion: QIVc was significantly more effective in preventing influenza-related and respiratory-related hospitalizations/ER visits, as well as all-cause hospitalizations, compared to QIVe-SD. Disclosures: Stephen I. Pelton, MD, Seqirus (Consultant) Maarten Postma, Dr., Seqirus (Consultant) Victoria Divino, PhD, Seqirus (Consultant) Joaquin F. Mould-Quevedo, PhD, Seqirus (Employee) Ruthwik Anupindi, PhD, Seqirus (Consultant) Mitchell DeKoven, PhD, Seqirus (Consultant) myron J. levin, MD, GSK group of companies (Employee, Research Grant or Support)